Penerapan Content Management System (CMS) Untuk Pengembangan Website Badan Kepegawaian dan Pengembangan SDM Kabupaten Empat Lawang - Dharma, Bobby Surya; Saputri, Nurul Adha Oktarini; Zaini, Kurniawan (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2024)
This study aims to solve the problems that exist on the website of the Human Resources and Personnel Development Agency of Empat Lawang Regency. Since 2018, this website has experienced minimal significant updates, causing information to become outdated and not in accordance with the needs of today's society. Limited features and unattractive designs also affect the user experience. Therefore, researchers will implement a Content Management System (CMS) for the development of this website. CMS allows users to create and manage websites easily, update content regularly, add new features, and design good websites. The results of this study produce an aesthetic, easy-to-navigate, and feature-rich website for accessing personnel information and human resource development. This website is also designed to be responsive and secure, supporting Empat Lawang Regency in improving the quality of service to its people